A new and old pandemic – the Burnout Syndrome - de Sousa, José Francisco (Revista JRG de Estudos Acadêmicos, 2022)
The Burnout Syndrome (SB) is known worldwide, but scientific studies only started from the researches made by the American psychologist Freudenberger. Its concept encompasses three dimensions: emotional exhaustion, depersonalization and low professional achievement. It is currently a student in various fields of human knowledge, from Anthropology to Psychology. The area of ​​Psychology that most researchers BS is the Psychodynamics of Work in which they call it "Malaise". However, researchers involving BS under the perspective of Behavior Analysis is scarce in Brazil and in the world. This study aims to analyze BS in several countries, from developed to poor countries, and in this sense supports the thesis that it is a pandemic. It is a study of a theoretical nature, of qualitative, descriptive and bibliographic nature and has as theoretical basis Skinner's Radical Behaviorism